2019
DOI: 10.18203/issn.2455-4510.intjresorthop20192092
|View full text |Cite
|
Sign up to set email alerts
|

Study of clinicoradiological and functional outcomes in intraarticular distal end radius fractures managed by volar locking plate

Abstract: <p class="abstract"><strong>Background:</strong> Various modalities of fixation are available for management of distal end radius fractures. Assessment of the functional and radiological outcomes of intra-articular distal end radius fractures managed with volar locking plate was attempted with the present study.</p><p class="abstract"><strong>Methods:</strong> In this prospective interventional study, thirty adult patients with closed distal radius fractures with intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…According to Liderstrom scoring, 53.3% of patients had excellent results. 5 Lakshman K et al operated 30 patients of distal radial fracture with open reduction and internal fixation with volar locking compression plate. Gartland and Werley demerit scoring was used to assess functionality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Liderstrom scoring, 53.3% of patients had excellent results. 5 Lakshman K et al operated 30 patients of distal radial fracture with open reduction and internal fixation with volar locking compression plate. Gartland and Werley demerit scoring was used to assess functionality.…”
Section: Discussionmentioning
confidence: 99%
“…1 Pravin Agrawal also demonstrated excellent functional outcome in 60% of his patients according to Mayo scoring. 5 Prem Kotian in his study demonstrated that there was no significant difference in radial shortening, decrease in palmer angulations and loss of radial deviation after three months follow up. Majority of the patients had a good outcome 60% followed by fair 25% and excellent in 15% according to Sarmiento's Modification of Landerstorm Criteria.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation